Feasibility study for application of the compressed-sensing framework to interior computed tomography (ICT) for low-dose, high-accurate dental x-ray imaging. (February 2016) - Je, U.K.; Cho, H.M.; Cho, H.S.; Park, Y.O.; Park, C.K.; Lim, H.W.; Kim, K.S.; Kim, G.A.; Park, S.Y.; Woo, T.H.; Choi, S.I.
Abstract: In this paper, we propose a new/next-generation type of CT examinations, the so-called Interior Computed Tomography (ICT), which may presumably lead to dose reduction to the patient outside the target region-of-interest (ROI), in dental x-ray imaging. Here an x-ray beam from each projection position covers only a relatively small ROI containing a target of diagnosis from the examined structure, leading to imaging benefits such as decreasing scatters and system cost as well as reducing imaging dose. We considered the compressed-sensing (CS) framework, rather than common filtered-backprojection (FBP)-based algorithms, for more accurate ICT reconstruction. We implemented a CS-based ICT algorithm and performed a systematic simulation to investigate the imaging characteristics. Simulation conditions of two ROI ratios of 0.28 and 0.14 between the target and the whole phantom sizes and four projection numbers of 360, 180, 90, and 45 were tested. We successfully reconstructed ICT images of substantially high image quality by using the CS framework even with few-view projection data, still preserving sharp edges in the images. Highlights: A study for the compressed-sensing (CS) framework to the interior CT (ICT) reconstruction is done. Systematic simulation works for the imaging characteristics is done. The CS framework seems very promising for the ICT reconstruction of high accuracy. The potential impacts of the ICT in clinical diagnosis are not clear at the present stage.